Prepare for IELTS : academic modules = Tài liệu luyện thi chứng chỉ IELTS - Todd, Vanessa. (Nxb Tp.HCM, 2000)
Introduction to the IELTS test. The listening test. The reading test. The writing test. The speaking test. Answers and tapescripts.